Instytucje i instrumenty polityki regionalnej. Zarys problematyki - Lotko, Katarzyna (The Institution and the Instruments of Regional Politicy. The Outline of the Problems, 2006)
The formation of regional politicy in Poland is in relevance with European structures' integration. The Polish accession to the European Union caused that there are a great many activities taken apio create some institutional background of regional politicy and the instruments of its realisation. There are a great many positive aspects of adjustment of regional politics integration. However, one can notice some disadvantages so there is a need for essential improvement. The main goal of this article is to present the institutions and instruments of regional politicy. There is huge relationship between structure and the working form of regional politicy. These institutions use the instruments and their status, authorisation and skills determine the effectiveness of regional politicy. The paper presents various institutions in Poland and the instruments which let them realise the regional politicy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 204-213